2014
DOI: 10.3402/iee.v4.24281
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of schistosomiasis and fascioliasis host snails along the Mara River in Kenya and Tanzania

Abstract: We purposively selected 39 sampling sites along the Mara River and its two perennial tributaries of Amala and Nyangores and sampled snails. In addition, water physicochemical parameters (temperature, turbidity, dissolved oxygen, conductivity, alkalinity, salinity and pH) were taken to establish their influence on the snail abundance and habitat preference. Out of the 39 sites sampled, 10 (25.6%) had snails. The snail species encountered included Biomphalaria pfeifferi Krauss – the intermediate host of Schistos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…This is because the water temperature, the water levels and water currents are more conducive than during the rainy season when the rains are heavy and wash away many of the snails [27,28]. Similar patterns of higher schistosomiasis prevalence in the dry season than the rainy season have also been reported in [25][26][27][28][29].…”
Section: Study Limitationmentioning
confidence: 73%
See 1 more Smart Citation
“…This is because the water temperature, the water levels and water currents are more conducive than during the rainy season when the rains are heavy and wash away many of the snails [27,28]. Similar patterns of higher schistosomiasis prevalence in the dry season than the rainy season have also been reported in [25][26][27][28][29].…”
Section: Study Limitationmentioning
confidence: 73%
“…Anto, Asoala [25] reported similar findings in Ghana. Additionally, dry season presents conducive environment for buildup of snail populations [26]. This is because the water temperature, the water levels and water currents are more conducive than during the rainy season when the rains are heavy and wash away many of the snails [27,28].…”
Section: Study Limitationmentioning
confidence: 99%
“…There is positive correlation between snail richness and built-up area class [9]. Gabriel et al [10] also reported activities associated with agricultural irrigation can cause adverse impacts on wetland ecological resources. Land-use change due to human settlement and his domesticated animals can affect water quality [11].…”
Section: Introductionmentioning
confidence: 99%
“…The other medically important snails collected was L.natalensis and is second dominant and abundant species. Moreover, studies of Gabriel et al[10] showed that L. natalensis was the dominant species followed by B. pfeifferi in river habitat. L. natalensis accounted for 16.45% of the snail collection and encountered 29.2% of the surveyed sites with prevalence of 69.6%, 24.7% and 2.1% in wetlands, rivers and irrigation ditches, respectively.…”
mentioning
confidence: 98%
“…Some of the snails transmitting the above infections like B. pfeifferi and B. globosus transmit Schistosoma parasites to man causing human Schistosomiasis (Brown, 1980;Gryseels, 1989;Jordan et al, 1993;Opisa et al, 2011;Dida et al, 2014) while, L. natalensis transmits Fasciola parasites to animals and man causing fascioliasis (Utzinger and Tanner, 2000;Dida et al, 2014). Biomphalaria pfeifferi is mainly found in tropical regions of Africa and Southwest Arabia.…”
Section: Introductionmentioning
confidence: 99%